ANALISIS PEMBUKTIAN DALAM PERKARA PEMBUNUHAN YANG DIRENCANAKAN DI PENGADILAN NEGERI JAKARTA SELATAN (STUDI KASUS PUTUSAN NO 309/PID.B/2023/PN.JKT.SEL) - Daniel Patar, Kevin; Sari, Indah (MALA IN SE: Jurnal Hukum Pidana, Kriminologi, dan Viktimologi, 2025)
Importance of Evidence in premeditated murder cases often involves complex and in-depth evidence. The problem formulation for this thesis is 1) How is the evidence in premeditated murder cases in the Criminal Code Laws and Regulations? And 2) Is Decision No. 309/Pid.B/2023/PN.Jkt.Sel is it in accordance with statutory regulations? The purpose of this research is to determine the evidence in premeditated murder cases in statutory regulations. This research method uses normative research, namely research carried out by analyzing written laws from library materials or secondary data. The results of this research concluded that evidence in premeditated murder cases in statutory regulations is regulated explicitly in Article 184 of the Criminal Procedure Code, namely witness statements, expert statements, letters, instructions and statements from the defendant. Conformity of Decision No. 309/Pid.B/2023/PN.Jkt.Sel with statutory regulations is in accordance with the elements of the offense committed by the defendant as stated in Article 355 paragraph (2) of the Criminal Code, namely the element of whoever commits serious abuse, which is carried out with prior planning, and the act causes death. After the stabbing, the victim was rushed to hospital and based on evidence from Visum et Repertum No. HK.06.03/VIII.1/75/2023 victim Stefanus Benny Sugiharto was found to have open wounds on his head, back, chest and limbs due to sharp and blunt violence, followed by skull fractures and brain bleeding due to sharp violence which could cause death.